2020
DOI: 10.5114/ait.2020.101216
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tracheostomy for long-term ventilated COVID-19-patients: rationale and first clinical-safe for all-experience

Abstract: Background COVID-19 infection has resulted in thousands of critically ill patients admitted to ICUs and treated with mechanical ventilation. Percutaneous tracheostomy is a well-known technique utilised as a strategy to wean critically ill patients from mechanical ventilation. Worldwide differences exist in terms of methods, operators, and settings, and questions remain regarding timing and indications. If tracheostomy is to be performed in COVID-19 patients, a safe environment is needed for optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Technical problem and difficulty in swallowing two complications of bronchoscope observed in two studies, both used disposable bronchoscopes [25]. Complications were more often due to PDT and tracheostomy leading to major or minor bleeding, delayed complications, cellulitis, infection and pneumothorax [71, 27, 80, 69, 81-84, 73]. Events valve migration, ETT dislodgement in patients was not associated to bronchoscopy [85, 49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical problem and difficulty in swallowing two complications of bronchoscope observed in two studies, both used disposable bronchoscopes [25]. Complications were more often due to PDT and tracheostomy leading to major or minor bleeding, delayed complications, cellulitis, infection and pneumothorax [71, 27, 80, 69, 81-84, 73]. Events valve migration, ETT dislodgement in patients was not associated to bronchoscopy [85, 49].…”
Section: Discussionmentioning
confidence: 99%
“…While interventional procedures like reduction in lung volume, hemostasis of active bleeding, intubation, extubation, tracheostomy, FBA, surfactant delivery, and decannulation provided positive outcome for the ICU patients under prolonged mechanical ventilation [13,26]. Percutaneous tracheostomy (PT) in the ICU patients is widely used to facilitate weaning from mechanical ventilation, to anticipate prolonged mechanical ventilation, to aid in the management of respiratory secretions and protect the airway in patients at risk of aspiration, to prevent laryngeal injury, and to minimize sedatives [27]. The therapeutic bronchoscopic procedure lasted for maximum 10 minutes, while guided PDT lasted for around 25-30 minutes for most of the COVID-19 patients [28][29][30].…”
mentioning
confidence: 99%
“…Manfaat trakeostomi pada intubasi lama adalah mengurangi volume dead space, menurunkan resistensi saluran pernafasan, menghindari terjadinya kerusakan laring, pita suara dan stenosis glotis dan subglotis (Murphy et al, 2021). Disamping itu memudahkan perawatan, memudahkan suction lendir, memudahkan transportasi dan kenyamanan pasien, lebih mudah berbicara kembali dan memberi sarana diet secara oral (Jonckheere et al, 2021).…”
Section: Diskusiunclassified
“… 9 Several smaller studies from earlier in the pandemic reported lower decannulation rates, ranging from 8% to 13%. 1 , 3 , 4 However, one of the largest systematic review and meta-analysis comprising over 3000 patients found an average decannulation rate of 34.9%. 7 One potential explanation for differences is lack of availability and willingness of long-term acute care hospital (LTACH) facilities to accept SARS-CoV-2 infected patients, wanting to wait for viral clearance before accepting patients for transfer.…”
mentioning
confidence: 99%
“…At the onset of the pandemic there were questions regarding the safety and value of tracheostomy for SARS-CoV-2 patients with prolonged respiratory failure. Tracheostomy has since been described and safely performed in these patients, and several societal guidelines support performing tracheostomy with proper personal protective equipment and precautions 1–6…”
mentioning
confidence: 99%